Factores asociados con la comprensión lectora en estudiantes del segundo grado de primaria de la Institución Educativa N°61023 Rosa Licenia Vela de Costa, Nauta 2024 - Navarro Murayari, Edith Elizabeth (2025)
The purpose of this research was to determine the relationship of associated factors (personal, sociocultural and pedagogical) with reading comprehension in elementary school students. A quantitative, non-experimental and cross-sectional methodology was applied, with a descriptive approach . Correlational to analyze the relationships between variables. The study population consisted of 88 students in the 2nd grade of primary school. Since we worked with the entire population, the sample was a census sample (100%). Data collection was done through structured questionnaires and a reading comprehension test. The main conclusions of this study revealed the following: There is a significant and high negative relationship between the associated factors: personal, sociocultural and pedagogical with reading comprehension. It is interpreted that, as the unfavorable condition increases, reading comprehension decreases. These results allow us to accept the hypothesis of the study, confirming the relationship between the associated factors and reading comprehension.